Nietzsche and Zion - Golomb, Jacob (Book collections on Project MUSE., 2004)
""Nietzsche's ideas were widely disseminated among and appropriated by the first Hebrew Zionist writers and leaders. It seems quite appropriate, then, that the first Zionist Congress was held in Basle, where Nietzsche spent several years as a professor ...